2020
DOI: 10.1088/1361-6641/ab9397
|View full text |Cite
|
Sign up to set email alerts
|

Optical, structural and electrical characterization of pure ZnO films grown on p-type Si substrates by radiofrequency magnetron sputtering in different atmospheres

Abstract: ZnO films were grown on p-type Si substrates by radio-frequency magnetron sputtering of ZnO target in pure argon or mixed argon-oxygen plasma and were investigated using atomic force microscopy, spectroscopic ellipsometry, Fourier-transformed infrared spectroscopy and electrical methods. It was observed that the films grown in argon plasma had large surface roughness which increases with the rise of deposition time. The lateral size of ZnO columns showed similar dependence on deposition parameters as the rough… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 63 publications
(120 reference statements)
0
2
0
Order By: Relevance
“…The simulation of the IRR spectra allows the estimation of the free carrier concentration (n 0 ), the mobility (l) and the film conductivity (r). As an example, the simulation of the spectrum for [Ge] = 20% was performed using the approach developed in [15,16] and the self-consistent parameters for SiO 2 , Al 2 O 3 and Ge, taking the electron effective mass value of 0.16m e . A good agreement was achieved between the experimental and simulated spectra (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The simulation of the IRR spectra allows the estimation of the free carrier concentration (n 0 ), the mobility (l) and the film conductivity (r). As an example, the simulation of the spectrum for [Ge] = 20% was performed using the approach developed in [15,16] and the self-consistent parameters for SiO 2 , Al 2 O 3 and Ge, taking the electron effective mass value of 0.16m e . A good agreement was achieved between the experimental and simulated spectra (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The optical properties of the films were studied using spectroscopic ellipsometry. The experimental spectra were analyzed within the two-layer model, with the upper (near the surface) inhomogeneous rough layer, and the bottom (adjacent to the Si substrate) homogeneous layer [27]. The upper layer was simulated within Bruggeman's model of effective medium, as a mixture of void space and ZnO, with parameters like those of a bottom layer.…”
Section: Optical Characteristicsmentioning
confidence: 99%
“…RF magnetron sputtering is also one of the most useful techniques for the fabrication of ZnO thin films with various dopants [21,25]. The diverse content of RE ions can be incorporated easily in a ZnO film, and its structural properties can be controlled by changing the sputtering conditions [26,27]. Specifically, it has been found that, through the varying of the nature of the gases used in the deposition process, the concentration of native point defects can be changed, and both the defect-related emission and the electrical conductivity of the film can be tuned [27,28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various deposition techniques for the deposition of ZnO films have been reported in the literature. Methods such as sol-gel [19], nanocluster-beam deposition [20], chemical bath deposition [21], plasma-assisted metal-organic chemical vapor deposition [22], RF-magnetron sputtering [23], successive ionic layer and adsorption reaction [24], spray pyrolysis [25], metal-organic chemical vapor deposition [3], AACVD [26,27] etc have been utilized.…”
Section: Introductionmentioning
confidence: 99%